(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The paradigma of equality contained in the Federal Constitution of 1988, not fulfilled in Brasil to this day, must be faced in public policies with the same determination that leaders employ to obey the dictates of market, neoliberalist and internationalized capital policies. The work will face the contrast of the global reality between developed and developing countries, especially Brasil, in terms of confronting politics, social and economic issues, emphasizing the need for, inte the latter (develpping) countries, turn attention to basic policies, income redistribution, and, therefore, transformative, which universalize the political debate and contribute to the desired equality at the starting point, whthout which the gap between the elite and poverty tends to be infinte and the nation’s progress without solution. The article will be developed using the analytical-deductive method, based on the analysis of legal, philosophical, political and sociological texts on the topic, published in books, magazines, periodicals and oficial repositories of national and international stricto sensu postgraduate programs.